The man who found time : James Hutton and the discovery of the Earth's antiquity - Repcheck, Jack (Basic Books, 2009)
There are three men whose life's work helped free science from the strait-jacket of religion. Two of the three--Nicolaus Copernicus and Charles Darwin--are widely heralded for their breakthroughs. The third, James Hutton, is comparatively unknown, yet he profoundly changed our understanding of the earth, its age, and its dynamic forces. A Scottish gentleman farmer, Hutton's observations on his small tract of land led him to a theory that directly contradicted biblical claims that the Earth was only 6,000 years old. This expertly crafted narrative tells the story not only of Hutton, but also of S.